Proceedings of the Ocean Drilling Program, 138 Scientific Results 1995
DOI: 10.2973/odp.proc.sr.138.147.1995
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Leg 138 Sediments and History of Hydrothermal Activity

Abstract: Three main sedimentary sequences are briefly characterized in geochemical terms. Metalliferous sediments have lower average contents of Fe, Mn, and combined microelements, and higher average contents of Ti and Al, than other recent and ancient metalliferous sediments of the Pacific Ocean. We propose the history of hydrothermal activity in the eastern equatorial Pacific for the last 17 m.y.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In Hole 851B substantial amounts of clay are distributed at depths 150 to 180 meters below seafloor (mbsf). A layer of metalliferous sediments at 317 m is indicative of hydrothermal activity approximately 9 Ma ago [ Gurvich et al , 1995]. Pore waters were extracted using a stainless steel squeezer.…”
Section: Samples and Analytical Methodsmentioning
confidence: 99%
“…In Hole 851B substantial amounts of clay are distributed at depths 150 to 180 meters below seafloor (mbsf). A layer of metalliferous sediments at 317 m is indicative of hydrothermal activity approximately 9 Ma ago [ Gurvich et al , 1995]. Pore waters were extracted using a stainless steel squeezer.…”
Section: Samples and Analytical Methodsmentioning
confidence: 99%
“…Pisias et al (1995) showed that the oceanic crust of this area has been formed similarly to the Dorado site on the East Pacific Rise (EPR) 17 Ma ago. The sedimentary sequence of the Guatemala basin is, as in core GC50, characterized by a basal metalliferous interval, which has been interpreted as a high-temperature hydrothermal plume deposit (Gurvich et al, 1995). Such deposits form close to the spreading axis in vicinity of high-temperature hydrothermal vents by precipitation of mineral particles within the mixing zone between plume and seawater.…”
Section: Formation Mechanismmentioning
confidence: 99%
“…The lowest of these values is more than fourfold higher than the average crustal Os concentration (Peucker-Ehrenbrink and Jahn, 2001). This approach over estimates detrital Os inventories because it neglects the fact that biogenic opal, not lithogenic matter, constitutes the bulk of the non-carbonate fraction (Mayer et al, 1992;Gurvich et al, 1995). A quantitative estimate of detrital Os in Site 849 sediments can be obtained using the fractions of the detrital materials in the sediments.…”
Section: Detrital Os Contributionsmentioning
confidence: 98%